The Role of Vitamin C Supplementation in Preventing Severity Progression in Mild and Moderate COVID-19 Patients at Universitas Airlangga Hospital - Arifandi, Yoga Akbar; Rosyid, Alfian Nur; Indiastuti, Danti Nur; Effendi, Wiwin Is (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: The administration of different dosages of vitamin C significantly yields different outcomes in preventing the progression of disease severity. Most patients with mild and moderate coronavirus disease (COVID-19) did not demonstrate an escalation in disease severity.   Abstract Introduction: Coronavirus disease (COVID-19) is an infectious disease that increases pro-oxidant elements and decreases antioxidants. Vitamin C functions as a potent antioxidant in humans due to its electron-donating properties.  This study aimed to explain the impact of three distinct vitamin C supplementation dosages in preventing disease severity progression among mild and moderate COVID-19 patients. Methods: This retrospective study used secondary data from 100 medical records (n=100). The subjects were classified into three categories based on the vitamin C dosage. The data were analyzed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 26.0 for Windows. Results: Most of mild and moderate COVID-19 patients (78%) did not experience increased disease severity. Vitamin C supplementation significantly demonstrated a different outcome in preventing disease severity progression among the three groups (p=0.018). However, it did not significantly show any difference in reducing the duration of hospital stay (p=0.680). Conclusion: The impact of vitamin C supplementation on COVID-19 severity appeared to vary depending on the dosage administered. However, it did not affect the duration of the hospital stay.